Identification and parameter estimation for electrical anisotropy in two-dimensional magnetotelluric models - Ji, Xiaojie; Xu, Zidong; Huang, Zejiao; Zhao, Wei; Liu, Ying (Frontiers in Earth Science, 2025)
When the subsurface media contain electrical anisotropic structure, magnetotelluric isotropic inversion fails to recover the electrical anisotropic structure and may distort the image of isotropic structures. Besides, due to the diversity and uncertainty in inversion caused by multi-parameterization, mature and practical anisotropic inversion procedure is lacking at the case with anisotropic angle. Here, four two-dimensional models were constructed with mixed electrical anisotropic/isotropic structures including azimuthal anisotropy case. Phase tensor and real induction vector analyses, as well as two-dimensional isotropic and one-dimensional anisotropic inversions, were performed to identify and estimate the electrical anisotropic parameters. Based on the equivalence concept of electrical anisotropy, the extracted anisotropic structure was equivalent to isotropic structure with alternating high- and low-resistivity anomalies. These equivalent anomalies were then added into two-dimensional isotropic inversion as a priori information. Consequently, the isotropic structure of the true model is well recovered. The proposed method can identify and estimate the electrical anisotropy structure as well as the isotropic structure to a certain extent in two-dimensional magnetotelluric models. This study provides a novel approach for analyzing electrical anisotropy in magnetotelluric data.